2017
DOI: 10.1007/s00464-017-5552-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical outcomes and quality of life between laparoscopic and open central pancreatectomy with pancreaticojejunostomy

Abstract: LCP with pancreaticojejunostomy is safe and feasible for benign or borderline malignant lesions in the pancreatic neck and proximal body. Compared to OCP, LCP is associated with lower estimated blood loss, faster recovery, and better quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 25 publications
0
37
0
4
Order By: Relevance
“…The present study used the new version of the International Study Group (ISGPS) de nition and grading of postoperative pancreatic stula [11]. Our pilot studies showed that the morbidity rates and PF rates of LE, LSPDP and LCP were similar to those of open surgery [14,15,16,18]. Therefore, we believe that it is not the type of technique (laparoscopic or open) but the patient's condition and the operation's di culty level that are associated with PF formation.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The present study used the new version of the International Study Group (ISGPS) de nition and grading of postoperative pancreatic stula [11]. Our pilot studies showed that the morbidity rates and PF rates of LE, LSPDP and LCP were similar to those of open surgery [14,15,16,18]. Therefore, we believe that it is not the type of technique (laparoscopic or open) but the patient's condition and the operation's di culty level that are associated with PF formation.…”
Section: Discussionmentioning
confidence: 92%
“…Hence, organ-sparing pancreatectomy has increasingly become an option to treat benign or low-grade malignant tumours to preserve the pancreatic parenchyma and spleen as much as possible. Zhang et al [14,15,18]reported that LE, LSPDP and LCP are safe and feasible for benign or borderline malignant lesions with a faster recovery. LCP is associated with better quality of life [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the first comparative studies between minimally invasive and open central pancreatectomy conducted by Song et al demonstrated longer operative time but shorter hospital stay for MICP [64]. Another similar report from Asia suggests less blood loss as well as shorter first flatus and diet start times following laparoscopic central pancreatectomy [65]. Quality of life parameters were higher for laparoscopy compared to the open approach yet without statistical significance.…”
Section: Other Minimally Invasive Proceduresmentioning
confidence: 99%